Advanced tutoring system to enhance students’ learning experiences - A conceptual enhanced business model - Marzuki, Amir Faris; Ramle, Mohammad Iqbal Hakim; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The objective of this paper is to provide a conceptual platform to enhance learning experience through mobile and web based platform for students targeted at primary and secondary schools in Malaysia. This conceptual systems, namely “ATSYS”, will require the participation of students (aged between 7 to 17) and qualified tutors. “ATSYS” is a business model which provides a platform where students can enhanced their learning experience thus helping them to excel in their studies. “ATSYS” also provides the opportunity for academic book publishers by providing them a platform to publish their business to the customers. Alternative and initial business model of Business Model Canvas (BMC) with 9 blocks of framework, literature review and value proposition canvas (VPC) have been used as the methodologies of this paper.